ECONOMIC FUNDAMENTALS OF THE NATIONAL TRANSPORT SYSTEM OF UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
The article examines how the economic foundations of the transport system of the Republic of Uzbekistan were organized during the years of independence based on the analysis of sources and literature. This study is of great importance in further improving the population and cargo transportation system in the Republic. For this purpose, the material and technical base of our country's transport system, airports, railway stations, and road infrastructures were studied which funds are involved in which conditions. It was determined that these activities will be carried out through executive funds of network organizations, material support provided by private sectors, direct investments of the Republic and foreign companies. In addition, in the period from 1991 to today, the reforms in the issue of providing the population with vehicles, their achievements and shortcomings are also covered in detail. In addition, the issue of transport by means of vehicles was evaluated analytically and critically at the national and international level. Opinions on the production and renewal of technical equipment, the continuous movement of airplanes, passenger and cargo trains, passenger and cargo cars, buses, trams, trolleybuses and metro trains used in the field are presented. This research can be used in educational institutions in the field of transport.